2017
DOI: 10.1016/s2214-109x(17)30341-8
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic costs potentially averted by tuberculosis control in India and South Africa: a modelling study

Abstract: SummaryBackgroundThe economic burden on households affected by tuberculosis through costs to patients can be catastrophic. WHO's End TB Strategy recognises and aims to eliminate these potentially devastating economic effects. We assessed whether aggressive expansion of tuberculosis services might reduce catastrophic costs.MethodsWe estimated the reduction in tuberculosis-related catastrophic costs with an aggressive expansion of tuberculosis services in India and South Africa from 2016 to 2035, in line with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 33 publications
0
55
0
2
Order By: Relevance
“…Globally, it is estimated that even with aggressive expansion of TB services (includes multi-drug resistant TB services and ACF), catastrophic costs would decrease only by 5–20% by 2035 (base year: 2015) [39]. Hence, countries need to move towards universal health coverage and social protection.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, it is estimated that even with aggressive expansion of TB services (includes multi-drug resistant TB services and ACF), catastrophic costs would decrease only by 5–20% by 2035 (base year: 2015) [39]. Hence, countries need to move towards universal health coverage and social protection.…”
Section: Discussionmentioning
confidence: 99%
“…Our estimate of direct cost is closer to the pooled estimate of US$61 considered as the direct cost of base care for drug-sensitive TB Care by Verguet et al . [14]. Another study from Chennai, India reported a mean total cost of US$48 [9].…”
Section: Discussionmentioning
confidence: 99%
“…Using a 10% of annual household income cutoff as threshold, 71.8% of the patients in Benin, West Africa experienced the catastrophic impact of TB [22]. With total costs ≥20% of household annual income, 39% Peruvian households incurred catastrophic costs [14]. They reported that only this threshold was most strongly associated with adverse TB outcome as against 10% or 15%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations